Discussion of An Independent Auditor's Ex Post Criteria for the Disclosure of Information - III, John H. Evans (Journal of Accounting Research, 1991)
John H. Evans III, Discussion of An Independent Auditor's Ex Post Criteria for the Disclosure of Information, Journal of Accounting Research, Vol. 29, Studies on Accounting Institutions in Markets and Organizations (1991), pp. 213-216